2019
DOI: 10.48550/arxiv.1904.00688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic text summarization: What has been done and what has to be done

Abdelkrime Aries,
Djamel eddine Zegour,
Walid Khaled Hidouci

Abstract: Summaries are important when it comes to process huge amounts of information. Their most important benefit is saving time, which we do not have much nowadays. Therefore, a summary must be short, representative and readable. Generating summaries automatically can be beneficial for humans, since it can save time and help selecting relevant documents. Automatic summarization and, in particular, Automatic text summarization (ATS) is not a new research field; It was known since the 50s. Since then, researchers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…One of the main drawbacks of the graph-based approach is that it doesn't consider the semantic structure of the sentence [29]. However, some researchers tried to handle this issue by taking into account additional language-dependent parallels, like semantic similarity [30]. Abdi et al [31] also proposed a query-based summary method that combines sentiment analysis and summarization approaches.…”
Section: ) Graph-based Approachmentioning
confidence: 99%
“…One of the main drawbacks of the graph-based approach is that it doesn't consider the semantic structure of the sentence [29]. However, some researchers tried to handle this issue by taking into account additional language-dependent parallels, like semantic similarity [30]. Abdi et al [31] also proposed a query-based summary method that combines sentiment analysis and summarization approaches.…”
Section: ) Graph-based Approachmentioning
confidence: 99%
“…We also adopt a selection verification mechanism to allow the authors of the paper to review the selected methods. Some survey works [30][31][32] are referenced to confirm that relevant approaches were not missed.…”
Section: Efficiency (Answering Rq4)mentioning
confidence: 99%
“…The study concluded that text summarization had made significant progress employing deep learning, however, the application of various deep learning architectures, parameters, and their respective impacts on results are yet to be analyzed. Aries et al30 reviewed different works of automatic text summarization and presented some problems and limits that prevent works from moving forward. In this paper, different classifications of automated text summarization are reviewed, which will help create a novel summary approach based on existing method classifications.…”
mentioning
confidence: 99%